Racialized parenting in the United States. Issue 8 (23rd June 2021) - Manning, Alex
Abstract: Contrary to anti‐black, cultural deficit logics that frame Black parenting as tied to the reproduction of social disadvantage, research shows that Black parents, and other parents of color, are agentic as they parent in direct response to the dominant racial order of the United States. In this paper, I review this scholarship and primarily focus on how Black parents approach raising children in the racialized worlds that they live in. To mitigate the disadvantages caused by racism, Black parents use various intentional racialized parenting approaches to instill in their children a resilience to a racist social world. The strategies used to cultivate resilience to racism exist in varied social and institutional contexts, and intertwine with how parents understand race, class, and identity. Laborious racialized parenting techniques do not solely matter at the micro‐level as such practices are unevenly recognized by white‐dominant social institutions. This uneven dynamic indicates how hegemonic norms of American parenting culture fit within a project of racial neoliberalism. Consequently, Black parents are structurally pushed to burden more responsibility to prepare their children to survive a deeply racist and hyper‐competitive social world with no guarantee that such intensive, strategic parenting will be rewarded.